Use of an Olmesartan Medoxomil‐Based Treatment Algorithm for Hypertension Control - Neutel, Joel M. (J Clin Hypertens (Greenwich), 2007)
Hypertension guidelines recommend a steppedcare approach that starts with titration of the initial agent followed by the addition of other agents, as necessary, to achieve goal blood pressure. This study assessed the effectiveness of an antihypertensive treatment algorithm with olmesartan medoxomil as the initial agent. This was a 24‐week, open‐label trial in patients (N=201) with mean seated diastolic blood pressure of 90–109 mm Hg. Following placebo run‐in, all patients received olmesartan medoxomil 20 mg/d for 4 weeks. At subsequent 4‐week intervals, the regimen was modified in patients with blood pressure >130/85 mm Hg: up‐titration of olmesartan medoxomil to 40 mg/d; addition of hydrochlo‐rothiazide 12.5 mg/d; up‐titration of hydrochlo‐rothiazide to 25 mg/d; addition of amlodipine besylate 5 mg/d; and up‐titration of amlodipine besylate to 10 mg/d. Patients who achieved blood pressure ≤130/85 mm Hg at any point exited the study with no further follow‐up. At Week 24, reductions in blood pressure from baseline were 33.7/18.2 mm Hg. Altogether, 87.7% of patients reached the goal blood pressure of ≤130/85 mm Hg and 93.3% achieved a blood pressure of ≤140/90 mm Hg. Thus, an antihypertensive algorithm with olmesartan medoxomil as the initial agent controlled blood pressure in the majority of patients, but with >60% of patients also requiring the use of a thiazide diuretic or a thiazide and a calcium channel blocker.